Perbandingan Penggunaan Metode Example Non Example dengan Metode Chain Writing pada Kemampuan Menulis Teks Deskripsi - Daffa Rifqi Mahardika (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
The writing of this thesis is motivated by the low ability of students in selecting vocabulary in learning Indonesian, especially in descriptive text material. In addition, the use of linguistic structures that are considered less causes low writing skills. In line with that, the lack of enthusiasm of students in learning Indonesian makes students difficult in making sentences. The purpose of this study is to determine the comparison of the use of the Example non Example learning method, and Chain Writing on students' abilities in writing descriptive text. The subjects of this study were students of class VII-A and VII-B of SMP Bintara Depok. Both classes were classified into the experimental group. The method focused on was Posttest-Only Control Group Design. The results obtained based on this study are that there are differences in the use of the Example non Example learning method and the Chain Writing learning method in learning descriptive text. This is supported by the achievement of scores obtained by students in the Example non Example method class (87.12) which is superior to the Chain Writing method class (76.43). Based on the results of the hypothesis test, the t count > t table is 5.511 (> 1.66757), and the sig. value. 0.000 (<0.05), it is concluded that Ha is accepted. Based on this, there is an influence of the learning method used in each experimental class. This research is expected to serve as a reference for consideration regarding policies and future research activities.